2017
DOI: 10.5114/pm.2017.66178
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of oestrogen receptors α and β in epithelium of the vaginal mucous membrane in women after oestrogen therapy

Abstract: Oestrogens act on target cells through α and β receptors (ERα and ERβ). Expression of oestrogen receptors is associated with the age and menopausal condition of women.The aim of the study was an immunohistochemical evaluation of ERα and ERβ receptors in epithelium of the vaginal mucous membrane of women subjected to different forms of hormonal therapy (HTM).Oestrogen receptors ERα and ERβ were identified using immunohistochemical methods and evaluated in smears of vaginal mucous membranes collected from 60 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Menopause in women initiates a period characterized by some changes caused by a physiological deficiency of estrogens. Vaginal epithelium undergoes thinning, the cells become flattened, their content of glycogen is reduced, and epithelial-connective papillae disappear ( Sawczuk, Gołębiewska, Mazurek, & Chyczewski, 2017 ). Marbut et al showed that 500 mg DPP powder supplementation for three months in 25 infertile men increased serum levels of LH, follicle-stimulating hormone (FSH), testosterone, and sexual desire; The authors concluded these effects might be due to the presence of steroid precursors in DPP ( Marbut, Al-Snafi, & Marbeen, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Menopause in women initiates a period characterized by some changes caused by a physiological deficiency of estrogens. Vaginal epithelium undergoes thinning, the cells become flattened, their content of glycogen is reduced, and epithelial-connective papillae disappear ( Sawczuk, Gołębiewska, Mazurek, & Chyczewski, 2017 ). Marbut et al showed that 500 mg DPP powder supplementation for three months in 25 infertile men increased serum levels of LH, follicle-stimulating hormone (FSH), testosterone, and sexual desire; The authors concluded these effects might be due to the presence of steroid precursors in DPP ( Marbut, Al-Snafi, & Marbeen, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…The α receptors being present principally in the epithelium, the stroma, and the muscle fibers, while β receptors predominate in the blood vessel endothelium. Besides, androgen receptors also are present in the epithelium and the stroma of the vagina (32)(33)(34).…”
Section: Genital Symptomsmentioning
confidence: 99%
“…Due to the bladder trigone and the urethra contain countless estrogen receptors decline in muscle mass and strength when serum estrogen declines provoke the postmenopausal women not to use hormonal therapy to have higher muscle damage ( 34 , 35 ).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…23 The difference in efficacy by route of administration may be due to the fact that topical estrogens lead to a greater ER increase in vaginal epithelium, compared with systemic preparations. 24 However, there is only low-quality evidence supporting the use of vaginal estrogen over placebo for GSM symptoms, as concluded in the most recent Cochrane review of 30 RCTs with over 6,000 women treated for atrophic vaginitis, a variably defined term. 25 This finding is consistent with the possibility that the effects of topical estrogens are limited to vaginal epithelium, causing maturation of the basilar cells and epithelial layer thickening, without an impact on vaginal stroma or vascularization.…”
Section: Decline In Estrogen and Genitourinary Syndrome Of Menopausementioning
confidence: 99%